Morphological and Variability Assessment of (F7) Wheat Lines Under Normal and Rainfed Conditions - Aziz, Khayyam; Abdur Rauf,; Yaseen,; Zaib, Muhammad Ismail; Muhammad Iqbal,; Naz, Amna; Beena,; Alam, Arzoo; Asama,; Afridi, Khilwat; Bibi, Haleema; Asim Ur Rahman,; et al. (Indus Journal of Bioscience Research, 2024)
A field trial was performed to identify the potential genotypes in 100 wheat lines (96 F7 fixed lines and 4 controls) for yield and yield-associated traits in an augmented design under irrigated and rainfed conditions. These lines/genotypes were analyzed for days to heading, days to maturity, plant height, grain per spike, thousand-grain weight and grain yield. The wheat genotypes showed a significant G×E for all the traits across irrigated and rainfed conditions. The evaluation of variances revealed significant differences among the wheat genotypes for the evaluated morphological traits. According to the findings of the present experiment genotype, the CCRIG7-82 showed the best performance in grain yield under normal conditions. However, wheat lines CCRIG7-1 surpassed all other genotypes in grain yield under rainfed conditions. Furthermore, wheat genotypes CCRIG7-1 showed stability of the traits i.e. days to maturity in both environments i.e. (irrigated and rainfed conditions). Different drought tolerance indices were evaluated for grain yield under rainfed (Ys) and irrigated (Yp) conditions. The stress tolerance (TOL) index identified CCR1G7-82 (8100 Kg ha-1), as the most tolerant, whereas, based on mean productivity, CCR1G7-59 and CCR1G7-60 (5900 Kg ha-1), were tolerant. Similarly, the geometric mean productivity (GMP) identified genotypes CCR1G7-60 (5246 Kg ha-1), as the best tolerant. In the same way, CCR1G7-85 (4716 Kg ha-1) were identified as tolerant genotypes based on harmonic mean (HM). Stress susceptibility index (SSI), grouped genotypes CCR1G7-64 (0.07), were stress tolerant. Stress tolerance index (STI) clustered genotypes CCR1G7-60 (5.87), as the most tolerant, while yield index (YI) ranked genotypes CCR1G7-76, CCR1G7-85 (1.71), as the most tolerant. The yield stability index (YSI) desirable genotypes were CCR1G7-64 (0.90) and were noted as drought tolerance genotypes in stressed conditions